(untitled) (ҚазҰУ хабаршысы. Экономика сериясы, 2020)
This study aims to explore generational differences in consumer attitudes towards sustainable business practices of hospitality and tourism firms. The empirical study adopts a quantitative research methodology based on survey data collection technique using a self-administered questionnaire. ANOVA tests were conducted to determine significant differences between four tested groups. The Tukey HSD test was used to conduct detailed multiple Post-hoc comparative analysis. Findings suggest that there is a significant difference between four generations in their attitudes regarding community and naturebased sustainable business practices of hospitality and tourism companies, while there is no difference regarding eco-friendly business concepts. This empirical quantitative research advances the generational theory as applied to hotel and restaurant business as well as tourism sectors by exploring behavioral differences and similarities between Baby boomers and X, Y, Z generational segments. On the other hand, it contributes empirical evidence to the holistic knowledge on generational consumer behavior in the under-researched context of Kazakhstan.